Aktivitas Ekstrak Daun Bangle (zingiber purpureum roxb.) Terhadap Pertumbuhan Bakteri Pseudomonas aeruginosa - Fajrin Noviyanto; Siti Hodijah; Yusransyah Yusransyah (State University of Gorontalo, 2020)
The bacteria that cause infections that can lead to high morbidity and mortality, the bacterium Pseudomonas aeruginosa. Bangle has a pharmacological activity as antibacterial, laxative, pancreatic lipase inhibitor, and protect cells from damage caused by oxidative stress. The purpose of this study are: to know the chemical constituents present in the extract of leaves bangle (Zingiber purpureum Roxb.) Can be efficacious as an antibacterial and knowing Minimal Inhibitory concentration (MIC) of the extracts of leaves bangle against Pseudomonas aeruginosa. Tests on the leaf extracts for antibacterial activity against Pseudomonas aeruginosa bangle made by the method of Kirby Bauer and solvents used are DMSO. Test solution with a concentration of leaf extract bangle 200, 400, 600, 800 and 1,000 ppm, the positive control solution (ciprofoxacin) and the solution negative control (DMSO). The results showed that the chemical constituents present in the extract of leaves bangle (Zingiber purpureum Roxb.) Are flavonoids, saponins, tannins, alkaloids and steroids. Value Minimum Inhibitory Concentration (MIC) of ethanol extract of the leaf bangle S bacteria Pseudomonas aeruginosa is a concentration of 40 % with an average diameter of 5.44 mm inhibitory. MIC extract ethanol extract of leaf bangle belonging to the bacterial activity that is strong enough..